2023
DOI: 10.3390/en16124587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clay Brick Waste Powder on the Fresh and Hardened Properties of Self-Compacting Concrete: State-of-the-Art and Life Cycle Assessment

Abstract: Sustainability and reducing environmental damage caused by CO2 emissions have become issues of interest to researchers in the construction sector around the world. Reducing the cement content in concrete by partially substituting it with by-products or waste falls within this field as the cement industry is responsible for 7% of global CO2 emissions. On the other hand, self-compacting concrete (SCC) is one of the special types of concrete that contains a large amount of powder (most of which is cement) to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…However, replacement of 100% fine NAs with fine RBAs [F(RBA) + C(NA)] in this mix resulted in a drop in compressive strength of 6.1%, while the drop in compressive strength was 8.9% when 100% fine NAs were replaced with fine RCAs [F(RCA) + C(NA)]. Since brick waste generally consists of aluminates and silicates, its pozzolanic characteristics [68] result in a significant drop in the compressive strength of concrete mix. Concrete mixes containing 100% fine and coarse RBAs attained 21.9% lower compressive strength compared to the control mix; however, the replacement of 100% coarse RBAs in this mix with coarse RCAs and coarse NAs increased the compressive strength by 2.6% and 20.3%, respectively.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…However, replacement of 100% fine NAs with fine RBAs [F(RBA) + C(NA)] in this mix resulted in a drop in compressive strength of 6.1%, while the drop in compressive strength was 8.9% when 100% fine NAs were replaced with fine RCAs [F(RCA) + C(NA)]. Since brick waste generally consists of aluminates and silicates, its pozzolanic characteristics [68] result in a significant drop in the compressive strength of concrete mix. Concrete mixes containing 100% fine and coarse RBAs attained 21.9% lower compressive strength compared to the control mix; however, the replacement of 100% coarse RBAs in this mix with coarse RCAs and coarse NAs increased the compressive strength by 2.6% and 20.3%, respectively.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Nasr et al [ 112 ] have conducted a comprehensive review of the LCA of the use of WBP in concrete. They found that by substituting waste brick powder into cement at different rates (0%, 12.5%, 25%, 37.5%, and 50%), there was a 10.8% to 43.2% reduction in global warming potential.…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…They found that by substituting waste brick powder into cement at different rates (0%, 12.5%, 25%, 37.5%, and 50%), there was a 10.8% to 43.2% reduction in global warming potential. According to a study, the manufacturing of clay brick waste reduced CO 2 equivalent emissions by 49% to 89% at rates ranging from 18.2% to 71.8% [ 112 ]. Fort et al [ 70 ] found that the best mixture made from waste brick dust could save up to 72% in greenhouse gases emitted compared to Portland cement paste, evaluated via a combined assessment of functional and environmental characteristics using the carbon dioxide emission efficiency index.…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…Self-compacting concrete (SCC) is a type of concrete that can be compacted without the need for external energy [19], offering numerous economic and technical advantages [20]. It is produced using the same fundamental ingredients as traditional concrete but incorporates significant amounts of superplasticizer additives, and, occasionally, viscosity-modifying additives, to achieve excellent workability [21]. It has recently emerged as one of the most important developments in the construction industry [22].…”
Section: Introductionmentioning
confidence: 99%